2016
DOI: 10.1021/acs.jpca.6b02925
|View full text |Cite
|
Sign up to set email alerts
|

Structural Control of Nonadiabatic Photochemical Bond Formation: Photocyclization in Structurally Modified ortho-Terphenyls

Abstract: Understanding how molecular structure impacts the shapes of potential energy surfaces and prospects for nonadiabatic photochemical dynamics is critical for predicting and controlling the chemistry of molecular excited states. Ultrafast transient absorption spectroscopy was used to interrogate photoinduced, nonadiabatic 6π cyclization of a collection of ortho-terphenyls (OTP) modified with alkyl substituents of different sizes and electron-donating/withdrawing character positioned on its central and pendant phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 63 publications
0
13
1
Order By: Relevance
“…The choice of stilbene is motivated by its interesting photochemistry, which includes cis/trans isomerization and electrocyclization pathways that represent the key reaction channels in many photochromic molecular switches. 13,[27][28][29][30][31][32][33][34] The 2PA spectroscopy of stilbene has been a subject of theoretical studies for several decades, 15,35,36 however, only a handful of studies have employed correlated many-body electronic structure methods. [37][38][39] To treat stilbene and larger conjugated systems, many studies employed semi-empirical approaches and timedependent density functional theory (TDDFT).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of stilbene is motivated by its interesting photochemistry, which includes cis/trans isomerization and electrocyclization pathways that represent the key reaction channels in many photochromic molecular switches. 13,[27][28][29][30][31][32][33][34] The 2PA spectroscopy of stilbene has been a subject of theoretical studies for several decades, 15,35,36 however, only a handful of studies have employed correlated many-body electronic structure methods. [37][38][39] To treat stilbene and larger conjugated systems, many studies employed semi-empirical approaches and timedependent density functional theory (TDDFT).…”
Section: Introductionmentioning
confidence: 99%
“…Excitation of the lowest energy transition of OTP (250−300 nm) results in the immediate appearance of two transient absorption bands peaking at 375 and 600 nm attributed to S 1 OTP. 33,34 Decay of OTP* is bimodal over the course of picoseconds, 31,32 with DHT formed as a result of excited-state deactivation. DHT exhibits two characteristic absorption features centered at 340 and 580 nm and is short-lived (45 ns) due to thermally activated ring reopening over a low energetic barrier (0.25 eV).…”
mentioning
confidence: 99%
“…OTP is structurally similar to diarylethenes, including cis -stilbene and many well-known photochromic dyes . Previously we investigated the photochemical dynamics that follow one-photon excitation of OTP through its lowest-energy optical transition; the absorption spectrum of OTP is plotted in Figure b. OTP in low-lying excited electronic states (OTP*) relaxes within a few picoseconds to yield trans -4 a ,4 b -dihydrotriphenylene ( trans -DHT, bottom left of Figure a); spectra of OTP* and trans -DHT are plotted in Figure b.…”
mentioning
confidence: 99%
“…Our understanding of OTP photochemistry derives from analysis of ultrafast pump–probe transient absorption (TA) data. We have previously observed that S 2 OTP* (which is populated on a time scale <100 fs) decays biexponentially with lifetimes of 700 fs and 3.0 ps in tetrahydrofuran (THF) solution. ,, However, we could not determine from TA which of these time scales corresponds with cyclization because the OTP* absorption spectrum completely spans that of S 0 trans -DHT, such that the kinetics of the photoproduct appearance cannot be determined unambiguously through global modeling of TA spectral dynamics . To resolve this issue, pump–repump–probe spectroscopy (PRP) was applied as a pathway-selective probe of dynamics .…”
mentioning
confidence: 99%
See 1 more Smart Citation